Borderless Nagykuns –a shared historical past and a (hoped-for) shared tourism future on Europe’s periphery - Kovács, Tibor; Kovács, Csaba; Vasvári, Mária (Acta Geographica Debrecina Landscape & Environment series, 2026)
This study examines the unified and historically traceable heritage system of the historical Nagykunság (Greater Cumania) (Hungary) and the communities that migrated to Bácska (Bačka) (Serbia) at the end of the 18th century. The relevance of the topic lies in reuniting cross-border cultural narratives, integrating spatially dispersed heritage elements, and leveraging digital interpretation tools. The research aims to analyze the expression of Nagykun (Greater Cumanian) identity within the diaspora and to establish the theoretical foundations for a future ”Nagykun Heritage Route”. Applied methods included the analysis of 23 semi-structured in-depth interviews conducted in Karcag, Kisújszállás, Bácskossuthfalva, and Pacsér, along with the study of demographic correlations using SPSS. Key results confirm that material heritage—especially gastronomy (e.g., mutton stew) and pastoral culture—shows stable continuity and high interpretability for tourism. In contrast, forms of intangible heritage—such as emigration narratives and ritual practices—have developed adaptively and require a more sophisticated threshold of interpretation. Bácska diaspora communities preserve more strongly narrativized identity structures, while in the mother country, traditions remain embedded in everyday practice. Digital tools play a key role in lowering the threshold of interpretation and ensuring virtual accessibility based on community participation.